2020
DOI: 10.1038/s41368-020-0076-8
|View full text |Cite
|
Sign up to set email alerts
|

miR-4651 inhibits cell proliferation of gingival mesenchymal stem cells by inhibiting HMGA2 under nifedipine treatment

Abstract: Drug-induced gingival overgrowth (DIGO) is recognized as a side effect of nifedipine (NIF); however, the underlying molecular mechanisms remain unknown. In this study, we found that overexpressed miR-4651 inhibits cell proliferation and induces G0/G1phase arrest in gingival mesenchymal stem cells (GMSCs) with or without NIF treatment. Furthermore, sequential window acquisition of all theoretical mass spectra (SWATH-MS) analysis, bioinformatics analysis, and dual-luciferase report assay results confirmed that h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 50 publications
(50 reference statements)
0
7
0
Order By: Relevance
“…Many studies show that miRNAs act directly or indirectly on transcripts encoding proteins related to cell proliferation and cell cycle [18]. To find the target of miR‐196b‐5p and further explain its molecular mechanism on WJCMSC proliferation, we conducted SWATH‐MS analysis in miR‐196‐5p inhibitors and the control groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies show that miRNAs act directly or indirectly on transcripts encoding proteins related to cell proliferation and cell cycle [18]. To find the target of miR‐196b‐5p and further explain its molecular mechanism on WJCMSC proliferation, we conducted SWATH‐MS analysis in miR‐196‐5p inhibitors and the control groups.…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs are kinds of noncoding single-stranded RNA molecules, which play a significant role in cell proliferation, cell apoptosis, cell cycle and differentiation by inducing target mRNA cleavage or translational inhibition [17][18][19][20]. Previously, our miRNA array data showed that some miRNAs, including miR-196b-5p, were differentially expressed in WJCMSCs, adipose-derived stem cells (ADSCs), BMMSCs, stem cells from apical papilla (SCAPs), dental pulp stem cells (DPSCs) and periodontal ligament stem cells (PDLSCs), which was confirmed by real-time quantitative RT-PCR (qRT-PCR) ( Fig.…”
mentioning
confidence: 99%
“…The levels of miR-140-3p were observed as previously stated. 56 Besides, following the manufacturer’s protocol (Invitrogen), 2 μg RNA sample was reverse transcribed into cDNA. The KMT5B primers are as follows: forward, 5′-GAGAAATGGAGGCAAGTTGTCT-3′; and reverse, 5′-ACATAGCGACTCTGTCCTTCA-3′.…”
Section: Methodsmentioning
confidence: 99%
“…MiR-140-3p mimic or mimic control along with the wild-type (wt) or mutant (mut) KMT5B 3′UTR-Luc reporter construct was then cotransfected into 293 T cells, as previously stated. 56 48 h later, luciferase enzymatic activities were then detected using the Dual-Luciferase Reporter Assay Kit (Vazyme).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation